2014
DOI: 10.3139/146.111034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2 in aluminum matrix on workability behavior of powder metallurgy composites during cold upsetting

Abstract: Effect of TiO 2 in aluminum matrix on workability behavior of powder metallurgy composites during cold upsetting Aluminum-based metal matrix composites withv arious weight percentages (0, 2.5, 5, 7.5, and 10) of TiO 2 reinforcementw eres ynthesized by means of powder metallurgy and theirw orkability behavior under triaxial stress-state conditions was completely studied during cold upsetting. Green cylindrical compactswere made using a400 kN hydraulic press with suitable punch and die, sintered at (590 ±10) 8 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…All the primary and secondary materials were 60µm in size. The composites were fabricated by powder metallurgy route [30]. A constant weight fraction of 5% copper was used in all the compositions.…”
Section: Methodsmentioning
confidence: 99%
“…All the primary and secondary materials were 60µm in size. The composites were fabricated by powder metallurgy route [30]. A constant weight fraction of 5% copper was used in all the compositions.…”
Section: Methodsmentioning
confidence: 99%
“…1(a). The required pressure was applied using hydraulic press of 400 kN capacities [11]. Graphite was used as lubricant to avoid sticking of powder to these surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that the addition of graphite serves to reduce hardness in copper-tin alloys and the low amount of graphite content was justified by the necessity to preserve mechanical properties. Ravichandran et al (2014) have revealed that uniform distribution of TiO 2 reinforcement was observed in Al matrix prepared by P/M method and found that there is decrease in porosity for Al-TiO 2 composites when compared with pure Al. Nickchi and Ghorbani (2009) have reported that at low duty cycles, the graphite content of the coating increases which tends to decrease the hardness as a soft phase and simultaneously the hardness of the bronze matrix increases and hence the overall hardness of the composite does not change considerably.…”
Section: Introductionmentioning
confidence: 94%